2006
DOI: 10.1007/s11032-005-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Disequilibrium Mapping of Morphological, Resistance, and Other Agronomically Relevant Traits in Modern Spring Barley Cultivars

Abstract: A set of 148 modern spring barley cultivars was explored for the extent of linkage disequilibrium (LD) between genes governing traits and nearby marker alleles. Associations of agronomically relevant traits (days to heading, plant height), resistance traits (leaf rust, barley yellow dwarf virus (BYD)), and morphological traits (rachilla hair length, lodicule size) with AFLP markers and SSR markers were found. Known major genes and QTLs were confirmed, but also new putative QTLs were found. The LD mapping clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 49 publications
1
87
0
2
Order By: Relevance
“…Further studies are required to test the present plant material in detail for its reaction to BYDV-MAV and the Cereal yellow dwarf virus-RPV. Furthermore, the eVect of the QTL on chromosome 2 detected by Kraakman et al (2006) should be analysed in combination with the Ryd2 and Ryd3 genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies are required to test the present plant material in detail for its reaction to BYDV-MAV and the Cereal yellow dwarf virus-RPV. Furthermore, the eVect of the QTL on chromosome 2 detected by Kraakman et al (2006) should be analysed in combination with the Ryd2 and Ryd3 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Ryd3 explaining about 75% of the phenotypic variance in the cross 'Vada' £ 'L94' has been mapped on chromosome 6H (Niks et al 2004). Furthermore, an association between SSR locus HVM054 on chromosome 2H and a large-eVect gene for BYD resistance or tolerance was reported in a linkage disequilibrium study in European spring barley (Kraakman et al 2006).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Association mapping offers a good alternative approach for detecting tightly linked markers to the QTL of interest in natural populations, germplasm collections, and even routinely generated breeding programs (Parrisseaux & Bernardo 2004;Abdurakhmonov & Abdulkarimov 2008). This method has been used in several plants species, including maize (Thornsberry et al 2001), barley (Kraakman et al 2006), hexaploid wheat (Breseghello & Sorrells 2006), sunflower (Darvishzadeh et al 2008;Davar et al 2012), chickpea (Saeed et al 2013), and long life span forest plants (Wilcox et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…It was first used as a candidate gene approach in plants by Thornsberry et al (2001), who demonstrated association between allelic variants and flowering time in the Dwarf8 gene in maize. It has been followed by other analyses in maize (Wilson et al 2004;Szalma et al 2005;, rice (Bao et al 2006a(Bao et al , 2006b), Arabidopsis thaliana (Olsen et al 2004;Aranzana et al 2005), barley (Ivandic et al 2002;Kraakman et al 2006), and wheat (Breseghello and Sorrells 2006b). The method is dependent upon LD (the nonrandom occurrence of alleles at different loci) between marker and phenotype, and this is affected by recombination.…”
mentioning
confidence: 99%